Accurate thermal buckling analysis of functionally graded orthotropic cylindrical shells under the symplectic framework. (August 2018) - Ni, Yiwen; Tong, Zhenzhen; Rong, Dalun; Zhou, Zhenhuan; Xu, Xinsheng
Abstract: Accurate thermal buckling analysis of functionally graded orthotropic cylindrical shells is presented based on the Reissner's shell theory under the symplectic framework. By introducing a full-state vector, the high-order governing differential equation is reduced into a set of low-order ordinary differential equations. The fundamental unknowns are expanded in terms of the symplectic eigensolutions without any trial function. The buckling equations and buckling mode shapes are analytically obtained. The present study demonstrates that the expressions of displacements have different forms and strongly depend on the end conditions and thickness. Some new results are presented in numerical examples. Graphical abstract: fx1 Highlights: An analytical method is proposed for thermal buckling of FG cylindrical shells. Exact solutions are represented by a series of symplectic eigensolutions. Thermal buckling equations and buckling mode shapes are analytical obtained. The solution procedure is rigorously rational without any trial functions. A detailed discussion on the expressions of displacements are presented.